Framework Report for incorporating Gender Equality and Social Inclusion (GESI) elements in Climate Information Services (CIS) - Mapedza, Everisto D.; Huyer, Sophia; Chanana, Nitya; Rose, Alison; Jacobs-Mata, Inga; Mudege, Netsayi N.; Homann-Kee Tui, Sabine; Gbegbelegbe, Sika; Nsengiyumva, Gloriose; Mutenje, Munyaradzi; Nohayi, Nina (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate Information Services have an opportunity to increase smallholder farmers' resilience against climate change and climate variability whilst enhancing their livelihoods. The AICCRA Zambia project through the agricultural data hub, training and drought and flood indicators provide solid evidence for enhancing smallholder farmer households. For the CIS to be gender inclusive and promote resilience for male and female farmers, development practitioners must ask questions at different stages to ensure that gender considerations and barriers are removed. The removal of barriers will enable women, youths, men and people with other vulnerabilities to have equal access to CIS to climate-proof their agricultural production. Climate services have great potential for transforming women's agricultural production in Zambia. If the CIS is built on a patriarchal ecosystem, this will further reinforce gender biases and stereotypes which will reinforce further marginalization of women.